2014
DOI: 10.3126/jnps.v34i1.9030
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events of Exchange Transfusion in Neonatal Hyperbilirubinemia

Abstract: Introduction: Jaundice is an important problem during neonatal period. When total serum bilirubin (TSB) level exceeds a critical limit, it crosses the blood brain barrier and results into bilirubin encephalopathy. The main aim of therapy for neonatal hyperbilirubinemia is prevention of bilirubin encephalopathy by phototherapy and/or exchange transfusion. The aims of this study were to evaluate the efficacy of exchange transfusion (ET) and observe the adverse events during and following three days of ET in neon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…The mean period of gestation of neonates in our study was 38.3 ± 1 weeks which was identical to available studies. [ 7 8 9 ] While mean age of presentation in our study was 98 ± 49 h, available literature has reported the age of presentation in days as 4 ± 1 days, 4.9 ± 2.2 days, and 111.6 ± 66 days. [ 7 8 10 ] This wide range in age of presentation can be explained due to differences in the basic etiology underlying hyperbilirubinemia such as ABO incompatibility, G6PD deficiency, and extravasation in the form of cephalhematoma.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…The mean period of gestation of neonates in our study was 38.3 ± 1 weeks which was identical to available studies. [ 7 8 9 ] While mean age of presentation in our study was 98 ± 49 h, available literature has reported the age of presentation in days as 4 ± 1 days, 4.9 ± 2.2 days, and 111.6 ± 66 days. [ 7 8 10 ] This wide range in age of presentation can be explained due to differences in the basic etiology underlying hyperbilirubinemia such as ABO incompatibility, G6PD deficiency, and extravasation in the form of cephalhematoma.…”
Section: Discussionmentioning
confidence: 73%
“…This was almost identical to the available literature. [ 8 9 10 ] All studies showed male preponderance among neonates with severe hyperbilirubinemia. Hence, male sex has emerged as a well recognized risk factor for exchange range hyperbilirubinemia in neonates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations